Evaluation of mobility models to mobile networks in emergency and rescue scenarios AVM, UPM, pursue, waypoint and brownian [Evaluación de modelos de movilidad para redes móviles en escenarios de emergencia y rescate: AVM, UPM, Pursue, Waypoint y Brownian] - Torres Tandazo, R. (2015)
Nodes in a mobile Ad Hoc network can change their location dynamically. The manner in which nodes can be moved can be represented by a mobility model. A mobility model defines the speed, pauses and direction of the nodes in a network. The way in which nodes move in an emergency scenario and rescue differs from a normal scenario, because the normal paths can be interrupted. AVM mobility models and UPM have been defined for this type of scenario. This paper presents a comparison of mobility models AVM, UPM, Waypoint, Brownian, Pursue on emergency and rescue scenario, with different routing protocols and different node density. The results show that Pursue, AVM and UPM models are more efficient than other models